Trzy wizje Ukrainy w twórczości Aleksandra Karola Grozy - Aleksandra Ewelina (Annales Universitatis Paedagogicae Cracoviensis. Studia Historicolitteraria, 2023)
In the article selected works of Aleksander Groza, a representative of “the Ukrainian school” of Polish romanticism, have been thoroughly investigated. The author used interpretive methods of postcolonialism, comparative studies and intertextuality, and sometimes also from the field of ethnography and ethnology. The article is an introduction to the monograph that the author is currently working on. As a result of the analysis of the works, it was possible to distinguish three main images of the Ukraine, which are stereotypical for the Polish literature in genere: Arcadian Ukraine, Cossack Ukraine and frenetic Ukraine. By using the fragments of Groza’s texts, as well as intertextual references, the author characterized each of these images. After outlining the poet’s profile through a simple biography, which will be developed in the future, the author of the article conducted an analysis and interpretation of the following works by Groza: the volume Poezje, Ukrainian elegies: Soroka and Pierwsza pokuta Żeleźniaka, poem Mogiły, dramas Śmieciński and Hryć. Such a versatile choice of texts allowed to draw some interesting conclusions concerning Aleksander Groza’z profile.